Inactivation of the Mla system and outer-membrane phospholipase A results in disrupted outer-membrane lipid asymmetry and hypervesiculation in Bordetella pertussis - Eline F. de Jonge; Lana Vogrinec; Ria van Boxtel; Jan Tommassen (Current Research in Microbial Sciences, 2022)
Bordetella pertussis is the causative agent of a respiratory infection known as whooping cough. With the goal of improving the production of outer-membrane vesicles (OMVs), we studied here the mechanisms that are involved in maintaining lipid asymmetry in the outer membrane of this organism. We identified homologues of the phospholipid (PL)-transport systems Mla and Pqi and of outer-membrane phospholipase A (OMPLA). Inactivation of mlaF, encoding the ATPase of the Mla system, together with pldA, which encodes OMPLA, resulted in an accumulation of PLs at the cell surface as demonstrated by the binding of a phosphatidylethanolamine-specific fluorescent probe to intact cells of this strain. The corresponding single mutations did hardly or not affect binding of the probe. These results are consistent with a retrograde transport directionality of the Mla system in B. pertussis and indicate that PLs accumulating at the cell surface in the mlaF mutant are degraded by OMPLA. Consequently, the mlaF mutant showed a conditional growth defect due to the production of free fatty acids by OMPLA, which could be compensated by inactivation of OMPLA or by sequestration of the produced fatty acids with starch. The mlaF pldA double mutant showed markedly increased OMV production, and representative antigens were detected in these OMVs as in wild-type OMVs. Further phenotypic characterization showed that the barrier function of the outer membrane of the mlaF pldA mutant was compromised as manifested by increased susceptibility to SDS and to several antibiotics. Moreover, inactivation of mlaF alone or together with pldA resulted in increased biofilm formation, which was, however, not directly related to increased vesiculation as the addition of purified OMVs to the wild-type strain decreased biofilm formation. We conclude that the absence of MlaF together with OMPLA results in PL accumulation in the outer leaflet of the outer membrane, and the increased vesiculation of the mutant could be useful in the development of novel, OMV-based pertussis vaccines.